Use of Academic Social Networking Sites by Academic Community at National Institute of Fashion Technology Centers in India: A Study - Jain, Sanjeev Kumar; Makwana, Jignesh (DESIDOC Journal of Library & Information Technology, 2022)
Academic social networking sites (ASNS) are trending in academics and play a significant role in disseminating knowledge. The study aims to explore the usage of ASNS by the faculty members and researchers of NIFT Centers across India. An online questionnaire method used to collect the primary data from 17 NIFT Centers. According to the results of the data analysis, the majority of respondents were aware of and utilised academic social networking sites (ASNS) in NIFT Centers. Google Scholar achieved the highest level of awareness and usage (34.98 %), followed by ResearchGate (27.09 %), Linkedin (18.23 %), and Academia.edu (17.24 %). The findings indicate that faculty members and researchers use ASNS primarily to access freely available millions of research papers, slightly less for communicating in a new way with researchers, and very rarely for increasing citations of research papers. Finally, the results reveal a positive attitude towards using famous academic social networking sites. NIFT should organise workshops and seminars on ASNS platforms to raise awareness and visibility of their research.